Mudança tecnológica, eficiência e produtividade total de fatores na agricultura brasileira, 1970-95 (Economia Aplicada, 2004)
This study applies a Data Envelopment Analysis (DEA) approach to analyze total factor, technology and efficiency changes in the Brazilian agriculture from 1970 to 1995, in the units of the federation. Malmquist productivity indexes were decomposed into two components: technical change and efficiency change. The results showed the largest productivity growths in the Center-west, Southeast and South regions. Technical progress was the most important factor in the areas of advanced-technology agriculture. Efficiency increases were the main components in areas of low-technology agriculture. The North and Northeast regions presented technical regress.